THEORETICAL APPROACH FOR DETERMINING AN EMISSIVITY OF SOLID MATERIALS AND ITS COMPARISON WITH EXPERIMENTAL STUDIES ON THE EXAMPLE OF 316L POWDER STEEL - Vasilevskyi, Oleksandr; Cullinan, Michael; Allison, Jared (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2024)
The work used Maxwell’s electromagnetic theory to quantitatively describe the emissivity of solid materials through electrical resistivity and temperature. An equation is proposed for recalculating the emissivity of smooth surfaces into powdery or rough surfaces. The obtained theoretical characteristics of the change in the emissivity of 316L powder steel were compared with experimental ones. As a result of the comparison, it was established that the experimental results obtained correlate with theoretical calculations and do not go beyond the limits of the expanded uncertainty of measurement.